Green logistics oriented tug scheduling for inland waterway logistics. (August 2021) - Zhu, Shengyan; Gao, Jiajing; He, Xueting; Zhang, Shuanglu; Jin, Ying; Tan, Zheyi
Abstract: Under the global consensus on reducing emissions, shipping companies are undertaking the social responsibility of greenhouse gas emission reduction. Meanwhile, it is a top priority for shipping companies to arrange the tugs and barges reasonably and achieve the goal of energy saving as well as emission reduction. Based on the above problem, this paper proposes a Mixed Integer Programming (MIP) model to jointly optimize the transport routes of tugs considering the barge transshipment, with the objective of minimizing the sum of the carbon emissions for barges handling, tugs travelling and waiting. In the view of specific problem, a Variable Neighborhood Search (VNS) algorithm is designed to solve this MIP model effectively. Numerical experiments based on different sizes of instances are implemented to validate the effectiveness of the proposed algorithm. Computational results indicate that the proposed model reduces carbon emissions by about 46.93% compared to the dispatching rule. Moreover, the consideration of barge transshipment in the model can reduce carbon emissions by about 10.46%. In addition, the VNS algorithm yields solutions with optimality gaps about 0.29% in a short time.